TEORI HERMENEUTIKA AL-QUR’AN FAZLUR RAHMAN - Zaprulkhan, Zaprulkhan (NOURA: Jurnal Kajian Gender dan Anak, 2017)
In general, hermeneutics is the art of understanding, translating and interpreting a foreign, distant, and dark discourse into something that is transparent, close, and understandable. In hermeneutics, it also assumes a triadic dialogue between the world of the text, the world of the outer and the world of the reader or the interpreter. So it is expected to produce a contextual reading and relevant to the condition of contemporary readers. Fazlur Rahman is one of the Muslim scientists who pioneered the use of the hermeneutical approach to recite the Qur’an contextually. Rahman uses hermeneutics in interpreting Qur’anic messages in order to respond to the challenges of the contemporary age. He carries the theory of double movement in interpreting the Qur’an is a movement from the present situation to Qur’anic times, then back to the present. The goal is none other than to seek the universal ideal value of the Qur’an that is universal to be compatible with the needs of contemporary society today. Therefore, this paper will discuss the theory of hermeneutics Al-Qur’an Fazlur Rahman. In order to be functional, it will further explore the application of the theory of Rahman’s double movement in interpreting polygamy discourse in the Qur’an.